2021
DOI: 10.1126/sciadv.abc4631
|View full text |Cite
|
Sign up to set email alerts
|

Do photosynthetic complexes use quantum coherence to increase their efficiency? Probably not

Abstract: Answering the titular question has become a central motivation in the field of quantum biology, ever since the idea was raised following a series of experiments demonstrating wave-like behavior in photosynthetic complexes. Here, we report a direct evaluation of the effect of quantum coherence on the efficiency of three natural complexes. An open quantum systems approach allows us to simultaneously identify their level of “quantumness” and efficiency, under natural physiological conditions. We show that these s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 76 publications
(105 reference statements)
0
20
0
Order By: Relevance
“…The exciton coherence has generated much interest in quantum biology owing to discovery of coherent oscillations in exciton-transfer complexes, which led to an assumption that quantum coherence drives an energy transfer in natural photosynthetic complexes, making them extremely efficient. …”
Section: The Excitonic “Zoo” In Organic Materialsmentioning
confidence: 99%
“…The exciton coherence has generated much interest in quantum biology owing to discovery of coherent oscillations in exciton-transfer complexes, which led to an assumption that quantum coherence drives an energy transfer in natural photosynthetic complexes, making them extremely efficient. …”
Section: The Excitonic “Zoo” In Organic Materialsmentioning
confidence: 99%
“…Studies have also shown that the coherence might be helpful in transport dynamics, but it does not contribute to the high efficiency of this exciton energy transport dynamics . Another recent study argues that the contribution from quantum coherence is minute at best in photosynthesis transport processes . Other than quantum coherence, quantum features like entanglement and quantum memory effects (non-Markovianity) have been explored additionally to find their impacts on this highly efficient transport process.…”
Section: Introductionmentioning
confidence: 99%
“…For over a decade, a lot of work has exposed the mechanisms of environmental noise-assisted quantum transport (ENAQT) [8][9][10][11][12], a phenomenon describing how incoherent processes from interactions with the environment around a system can improve energy transport in quantum systems. This work was heavily motivated by the possible connection between ENAQT and the efficiency of photosynthesis [1,3,[8][9][10][13][14][15], though recent work suggests the relationship between the two may be more nuanced [16][17][18].…”
Section: Introductionmentioning
confidence: 99%